Centralised–decentralisation: State program of poverty reduction for ethnic minorities in Vietnam’s northern upland region - Lam, Minh Chau (The Australian journal of anthropology, 2020)
Building on ethnographic fieldwork in Vietnam’s northern upland region, this article uses the case of state programs of poverty reduction for the country’s ethnic minorities to add insights to scholarly understandings of the composition and workings of socialist states in today’s Asia. Scholars have widely rejected the idea of Asian socialist states as monolithic, totalising entities in favour of seeing those states as internally divided. However, they have mostly examined how Asian socialist states are divided vertically into the central government and local authorities, which either manipulate central policies for local interests or side with villagers to defy central superiors. The approach leaves the central government relatively intact as a unified, coherent whole. This article argues that the Vietnamese state is equally divided at the central level by documenting ethnographically the striking lack of coordination and synchronisation amongst central agencies responsible for implementing poverty reduction programs. This dysfunction is caused by what I term ‘centralised–decentralisation’, meaning that each of those central agencies has remarkable autonomy to decide how to implement the programs assigned to them, even in ways in conflict with other central state organisations.